Using ICT Tools and Technological Applications in this Era of the COVID-19 Pandemic to Facilitate Learning - Ohei Kenneth N (Holistica, 2023)
The globe is shaken by the abrupt emergence of the deadly Coronavirus Disease 2019 (COVID-19) pandemic. The global education system has been put to the test by this circumstance, which compelled educators to quickly adopt Information & Communication Technology (ICT) tools and technologies to support instruction. Although, great attempts are made by scholars to study the implications of Coronavirus Disease 2019 on the higher education curricular, there is dearth of previous studies regarding the impact of Information & Communication Technology tools and technological applications to foster learning amid Coronavirus Disease 2019 outbreak. This exploratory study therefore uses a meta-synthesis approach and visited relevant literatures as lens to primarily examine the need to use Information & Communication Technology tools and technology applications to enhance learning in the Coronavirus Disease 2019 age. The research also shed some insight on the difficulties involved with employing Information & Communication Technology tools and technical applications to aid learning in times of pandemic and catastrophes, and it offers potential answers to educational institutions on how to handle these complications. The study’s findings suggest that Information & Communication Technology tools and technologies are the magic bullet for optimizing learning in times of disaster like the Coronavirus Disease 2019 pandemic. The study also shows that by overcoming some technical and financial obstacles like high cost of technology devices, electricity problems, lack of expertise, etc., the lessons learnt from the abrupt and compulsory adoption of Information & Communication Technology tools and technologies to lessen the negative effects of the disaster on learning amid Coronavirus Disease 2019 global emergency will help create new opportunities for the use of blended learning approaches to meet the needs of the Coronavirus Disease 2019 disruption and future learning deliveries.